Latent fingermark development on fired and unfired brass ammunition under controlled and blind conditions. (August 2022) - Lam, Rolanda; Hockey, Daniel; Williamson, Julie; Hearns, Nigel G.R.
Abstract: There has been growing interest in the Foster+Freeman RECOVER® Latent Fingerprint Technology system to develop fingermarks from fired ammunition. Over a six-month period, 1540 fingermarks were deposited on brass.223 ammunition, the majority of which were then fired after different time intervals. Samples were subjected to a cleaning protocol and/or processed with disulfur dinitride, cyanoacrylate/Brilliant Yellow 40, and/or vacuum metal deposition. Overall, 121 out of 1304 (9.3%) of natural fingermarks deposited were deemed identifiable post-firing and processing. This translated to 102 out of 652 (15.6%) of fired cartridges having identifiable fingermarks. A pseudo-operational study, which involved processing 1000 fired brass ammunition of various caliber using disulfur dinitride with and without a cleaning protocol, was conducted; only 18 (1.8%) comparable fingermarks were developed. This study demonstrates the need for more robust research involving this challenging substrate and novel technology, with which several issues were identified. Highlights: Fingermark recovery from fired ammunition remains challenging regardless of method. Disulfur dinitride able to develop additional fingermarks post-conventional methods. Difficult to reproduce laboratory study results in pseudo-operational scenario. Multiple issues encountered with Foster+Freeman RECOVER® LFT system and precursor.